Penentuan Rute Distribusi Feasible untuk Vehicle Routing Problem with Time Windows dengan Metode Sequential Insertion Pada CV. Hagia Mitra Mandiri - Prayoga Hidayat; Winarno; Wahyudin (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
CV. Hagia Mitra Mandiriis a company that distributes black queen bee honey products. Problems faced by CV. Hagia Mitra Mandiri in the distribution of its products, namely that the company has not yet planned product delivery routes to various customers of bitter black queen beehoney in the Jakarta, Bogor, Depok, Bekasi and Karawang areas. As a result, product delivery routes often exceed customer working hours, which can make delivery schedules less than optimal in terms of distance, travel time and delivery costs. This research aims to design the route that each vehicle must take according to the user's working hours, with the aim of optimizing the total travel distance. The method used is the sequential insertion algorithm method to solve the Vehicle Routing Problem with Time Windows problem model. The sequential insertion method is used to plan proposed distribution routes by considering travel distance, travel time and transportation costs. The research results show that there are differences in the proposed route from the initial route. The proposed route resulting from the calculation of the sequential insertion algorithm method produces the best distance, namely 307 km with a savings ratio of 18.13%, a comparison of total transportation cost savings of Rp. 58,758 and the difference in fuel usage is 7.55 liters. The total travel time is 667 minutes and the total travel time ratio is 9.01%.